Hypoxia Induces Connective Tissue Growth Factor mRNA Expression - Lee, Young Ki (The Korean Academy of Medical Sciences, 2009)
Connective tissue growth factor (CTGF) is known to be a profibrotic growth factor, which mediate the fibrotic effect of transforming growth factor-β (TGF-β) and to stimulate cell proliferation and matrix production. CTGF has been shown to be hypoxia-inducible in several cell types. Here we investigated the effect of hypoxia on CTGF gene expression in cultured mouse renal tubular cells (MTC). Quiescent cultures of MTC were exposed to hypoxia (1% O(2)) or normoxia in serum-free medium. The effects on hypoxia-induced CTGF expression were evaluated by Northern blot and real-time PCR. The roles of mitogen-activated protein kinase (MAPK) and TGF-β were also determined using specific biochemical inhibitors. Exposure of quiescent tubular cells to hypoxia for 24 hr in a conditioned medium resulted in a significant increase TGF-β. Hypoxia caused a significant increase in CTGF mRNA expression in MTC. Either JNK or ERK inhibitor did not block the hypoxia-induced stimulation of CTGF, whereas an inhibitor of p38 MAPK reduced the hypoxia-induced changes of CTGF. Although hypoxia stimulated TGF-β production, neutralizing anti-TGF-β1 antibody did not abolish the hypoxia-induced CTGF mRNA expression. The data suggest that hypoxia up-regulates CTGF gene expression, and that p38 MAPK plays a role in hypoxic-stimulation of CTGF. We also demonstrated that hypoxia induces CTGF mRNA expression via a TGF-β1-independent mechanism.